2001
DOI: 10.2190/q8bw-raa7-f2h3-19bf
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Issues in the Recruitment of Primary Care Patients with Depression

Abstract: The recruitment of male and older primary care patients is complicated by their tendency to refuse participation in WR screening for a treatment-outcome study of milder depression. Although each recruitment strategy offers advantages and disadvantages, the simultaneous use of both is recommended to recruit the most patients in the least amount of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…This hybrid method has been recommended as a strategy for balancing between recruitment efficiency and representativeness in health services intervention trials. 27 To be eligible, subjects had to be on the active patient roster at the CMHC, have a severe mental illness, 28 and have the capacity to provide informed consent. Inclusion criteria were purposely kept broad to optimize generalizability to other community mental health settings.…”
Section: Methodsmentioning
confidence: 99%
“…This hybrid method has been recommended as a strategy for balancing between recruitment efficiency and representativeness in health services intervention trials. 27 To be eligible, subjects had to be on the active patient roster at the CMHC, have a severe mental illness, 28 and have the capacity to provide informed consent. Inclusion criteria were purposely kept broad to optimize generalizability to other community mental health settings.…”
Section: Methodsmentioning
confidence: 99%
“…International comparative epidemiological studies in primary care are particularly rare and are hampered by a number of deficits (Ü stün and Sartorius, 1995;Nazemi et al, 2001;Katon and Schulberg, 1992;Wittchen et al, 2001a and b). Nevertheless, the available evidence from studies conducted in the 1980s and early 1990s in various countries (Katon and Schulberg, 1992) have suggested that depression in primary care is relatively common.…”
Section: Introductionmentioning
confidence: 99%
“…That said, we were aware that studies like ours, involving waiting room screening, may offer a less popular mode of recruitment to older people (relative to recruitment by GP). 3 The latter method would clearly not have been appropriate in our study, but the option to take home materials may have helped to minimise this effect. Bahri and Hilton's inappropriate extrapolation of our statistics ('this suggests that almost no participants were over the age of 65 years') is wholly incorrect.…”
Section: Authors' Responsementioning
confidence: 88%